Analysis of human nutrition imagery content in Science textbooks approved by the National Textbook Program 2014 - Bianco, André Amaral Gonçalves (ABCS Health Sciences, 2015)
Introduction: Changes in eating habits and lifestyle of the population in recent decades have contributed to the increased number of cases of overweight and obesity. Nutrition education is strategically important to face this problem and in Brazil is recent concern for nutrition education. Even after decades of debate on this subject is still scarce the number of suitable teaching materials. Objective: In this study we aimed to analyze quantitatively and qualitatively the images of nutrition education textbooks approved in the National Textbook Program (PNLD). Methods: A descriptive cross‑sectional study in which we used the method of content analysis. Nine collections of Sciences textbooks approved by PNLD 2014 were analyzed. Results: The analysis of nine collections of Sciences textbooks approved by the PNLD 2014 revealed flaws in imagery content. 328 images with distinction were found to the issues anatomy and physiology of the digestive system, rather than submitting to the related overweight and obesity content. Regarding the diseases associated with nutrition, they are still emphasized pathologies traditionally presented in textbooks, such as goiter. Conclusion: There is a need for revision of this imagery content in textbooks to have it as a contribution to the fight against overweight and obesity.